2014
DOI: 10.1073/pnas.1400749111
|View full text |Cite
|
Sign up to set email alerts
|

Control of MT1-MMP transport by atypical PKC during breast-cancer progression

Abstract: Dissemination of carcinoma cells requires the pericellular degradation of the extracellular matrix, which is mediated by membrane type 1-matrix metalloproteinase (MT1-MMP). In this article, we report a co-up-regulation and colocalization of MT1-MMP and atypical protein kinase C iota (aPKCι) in hormone receptor-negative breast tumors in association with a higher risk of metastasis. Silencing of aPKC in invasive breast-tumor cell lines impaired the delivery of MT1-MMP from late endocytic storage compartments to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 55 publications
(66 reference statements)
4
75
0
1
Order By: Relevance
“…We hypothesize that lack of an endosomal pool of MT1-MMP may limit subsequent delivery to invadopodia precursors in Endo II KD TNBC cells. It is worth noting that the Endo II binding partner Dynamin has recently been implicated in the formation and fission of tubulovesicular carriers from this intracellular pool of MT1-MMP (44). Like our findings here for Endo II, Dynamin was also identified as a positive regulator of invadopodia formation and cell invasion in MDA-MB-231 cells (45).…”
Section: Discussionsupporting
confidence: 82%
“…We hypothesize that lack of an endosomal pool of MT1-MMP may limit subsequent delivery to invadopodia precursors in Endo II KD TNBC cells. It is worth noting that the Endo II binding partner Dynamin has recently been implicated in the formation and fission of tubulovesicular carriers from this intracellular pool of MT1-MMP (44). Like our findings here for Endo II, Dynamin was also identified as a positive regulator of invadopodia formation and cell invasion in MDA-MB-231 cells (45).…”
Section: Discussionsupporting
confidence: 82%
“…Perhaps GPCRs and heterotrimeric G proteins release other such entities. In addition, MMP14 and RTKs have been implicated in other cellular responses and disease settings (4,(43)(44)(45). We speculate that the activation of MMP14 by heterotrimeric G proteins may contribute to such responses and diseases and that therapeutic approaches designed to block heterotrimeric G protein-mediated activation of MMP14 may be useful in such settings.…”
Section: Discussionmentioning
confidence: 96%
“…MT1-MMP has been referred to as a multi-functional protein involved in ECM degradation, angiogenesis and MMP-2 activation [28] and promotes tumor invasion [29]. Recently, it has been reported that MT1-MMP accumulates at the leading edge of invasion and invadopodia which are actin-rich membrane protrusions specialized for ECM degradation during cell invasion [30,31], and the recruitment of the cytoskeletal protein cortactin and MT1-MMP is pivotal for the maturation of functional invadopodia [32].…”
Section: Discussionmentioning
confidence: 99%